The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.2478/prilozi-2020-0009
|View full text |Cite
|
Sign up to set email alerts
|

Side Effects of Intravenous Patient-Controlled Analgesia with Remifentanil Compared with Intermittent Epidural Bolus for Labour Analgesia – A Randomized Controlled Trial

Abstract: Introduction: Epidural analgesia is considered a gold standard in obstetric anaesthesia and analgesia. However, in situation when it is contraindicated, unwanted by the patient or simply unavailable, remifentanil can be an excellent alternative. The goal of our study is to analyse the side effects of intravenous patient-controlled analgesia (IV PCA) with remifentanil compared with epidural analgesia during delivery. Material and methods: This study included 155 pregnant women in term for birth, divided into 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…An additional four records were identified by searching the grey literature, and one final record was obtained by correspondence with a trial author (P. Steer, personal communication, 2021). Thus, a total of 42 records 11 , 12 , 13 , 14 , 15 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 – representing 34 studies and including a total 10 221 participants – are included in the review.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional four records were identified by searching the grey literature, and one final record was obtained by correspondence with a trial author (P. Steer, personal communication, 2021). Thus, a total of 42 records 11 , 12 , 13 , 14 , 15 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 – representing 34 studies and including a total 10 221 participants – are included in the review.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies evaluated various methods of reducing epidural dose: intermittent administration, 11 , 12 , 80 lower dose formulations, 56 , 67 , 83 automated bolus regimens, 66 , 68 , 73 , 74 delayed administration, 71 reduced rate administration, 52 or local anaesthetic only with no spinal analgesia component. 72 Eight compared alternative methods of analgesia, 54 , 57 , 60 , 64 , 69 , 77 , 78 , 82 one evaluated additional epidural opioid, 65 two trials evaluated either warming the epidural solution 59 or using a heated neck warmer, 74 and two trials evaluated methods of acupuncture. 51 , 55 Three trials evaluated steroid 13 , 85 , 87 prophylaxis, two trials evaluated paracetamol 14 , 58 prophylaxis, and one trial evaluated antibiotic 15 prophylaxis.…”
Section: Resultsmentioning
confidence: 99%
“…This was evidenced by a study from Tugrul et al [24], demonstrating that the levels of umbilical cord CO 2 , O 2 , and pH showed no evident difference between the EA group and no analgesia group. Another study also found the levels of pH were comparable in both EA and no analgesia groups [25]. In a study including multiparas who had cesarean section experience, the neonatal umbilical arterial blood pH value in the EA group was better than the control group [26].…”
Section: Discussionmentioning
confidence: 99%
“…One of the main findings of this study was that when the uterine orifice was completely open, 8 h postdelivery and 24 h postdelivery, the VAS was low in the EA group compared with the no analgesia group. In a clinical prospective case-control study from Deshmukh et al [23], the data indicated that pregnant women had excellent satisfaction in terms of pain relief by the application of EA, and the VAS was decreased from 7.94 at 0 min receiving EA to 1.94 at the second stage of labor in multiparas [25].…”
Section: Discussionmentioning
confidence: 99%
“…After reviewing 75 full-text articles, we further excluded 64 trials that did not meet the inclusion criteria. Finally, eleven studies were included and analyzed in this meta-analysis [20][21][22][23][24][25][26][27][28][29][30].…”
Section: Study Selectionmentioning
confidence: 99%